Radial growth dynamics of selected tropical pioneer and succeeding tree species grown in Peninsular Malaysia - Wang, Kang Han; Sahri, Mohd Hamami; Salleh @ Japri, Mohd Nazre (Faculty of Forestry, Universiti Putra Malaysia, 2013)
The lack of distinct growth rings in tropical trees has caused difficulties in estimating their growth rates under natural conditions. This has resulted in limited knowledge concerning tropical tree growth. This study was conducted to assess the radial growth and cell production rate of three selected tropical species which are Macaranga gigantea, Endospermum diadenum and Dipterocarpus costulatus. The results showed that radial growth and cell production rate varied across species and tree size. Both pioneer species, M.gigantea and E.diadenum showed relatively faster radial growth rates in smaller diameter class. D.costulatus which belongs to succeeding species had relatively faster radial growth rate in larger diameter class.